I08 Nanoparticle based CRSIPR/CAS gene editing system to treat huntington's disease. (September 2018) - Rohiwal, Sonali S; Klima, Jiří; Vaškovičová, Michaela; Senigl, Filip; Šlouf, Miroslav; Pavlova, Ewa; Štěpánek, Petr; Stieger, Knut; Ellederova, Zdenka
Abstract : Background: The CRISPR/Cas system represents a pioneering gene editing technology for the treatment of monogenic disorders, employing R-Cas9 to target repetitive RNAs such as CAGN repeats suggests suitability in Huntingotn´s disease (HD) therapy. Till date, gene editing has been mediated primarily by viral vectors, but nanoparticles recently gained importance as carriers for delivery systems. They represent a promising technology to transfer RNA, protein and template to the targeted cells, due to their capacity to carry large sizes when used as vehicle. Moreover, the unlimited number of particles can be transferred with minimum host immune response and the potential to the cross blood brain barrier. Aim: We aim to develop a non-viral delivery system using nanoparticles for the in vitro and in vivo delivery of the R-Cas9 system and sgRNAs to enable genome editing in HD. Methods: We engineered CRISPR/Cas9 encapsulated poly (l-lactic) glycolic acid (PLGA) nanoparticles (NPs) by double emulsion and human serum albumin (HSA) NPs by desolvation method. The NPs were characterized by dynamic light scattering, zeta potential measurements and transmission electron microscopy. Next, we used a stable HEK293 cell line expressing the traffic light reporter (TLR-3) system to show efficient homology- directed repair (HDR) and non-homologous end joining (NHEJ) events following transfection with NPs. Results: CRISPR/Cas9 encapsulated PLGA NPs as well as HSA NPs have been synthesized with the particle size around ˜ 100–200 nm in diameter. The dynamic light scattering and zeta potential measurements showed that both NPs were monodispersed and have good colloidal stability. Nevertheless, the PLGA NPs showed a higher transfection efficiency and HDR as well as NHEJ events compared to HSA NPs. Conclusions: This study represents a promising step in the development of safe gene therapy approach for HD.